To simplify the expression \((3x - 8) + (2x + 5) - (4x - 8)\), follow these steps:
-
Distribute any negative signs: \[ (3x - 8) + (2x + 5) - 4x + 8 \]
-
Combine like terms:
-
Combine the \(x\) terms: \(3x + 2x - 4x\) \[ 3x + 2x - 4x = (3 + 2 - 4)x = 1x = x \]
-
Combine the constant terms: \(-8 + 5 + 8\) \[ -8 + 5 + 8 = (-8 + 8) + 5 = 0 + 5 = 5 \]
-
Putting it all together, the simplified expression is: \[ x + 5 \]
Thus, any expression that is equivalent to \(x + 5\) is considered equivalent to the original expression \((3x-8) + (2x+5) - (4x-8)\).
Examples of equivalent expressions could be:
- \(x + 5\)
- \(5 + x\)
- Any other rearrangements or expressions that simplify to the same result, such as \(1x + 5\).
If you provide specific options, I can confirm which of them are equivalent.